Interação de genótipos de milho vs locais, anos e épocas de semeadura - Buzinaro, Rodolfo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work aims to evaluate the G x E interaction and its unfolding in simple and complex part, in order to study the best locations and sowing dates for evaluation of genotypes grain yield of maize, at Jaboticabal-SP and Campo Alegre de Goiás-GO. Four experiments were carried out in randomized blocks design with three replications and 17 genotypes where 13 are experimental synthetic, three varieties and a commercial hybrid. Two seasons of cultivation were evaluated for each location. Environmental stratification was measured by the traditional method of Lin (1982) and the dissimilarity has been estimated by the method of Cruz & Castoldi (1991), in addition to the Pearson correlation coefficient between environments pairs. The results showed that there was disagreement between the methods used. Breeding programs must prioritize evaluations in years and locations to the detriment of different sowing dates in order to discriminate the best genotypes and make precise recommendations

O objetivo desta pesquisa foi avaliar a interação G x A e seu desdobramento em parte simples e complexa, a fim de estudar quais os melhores locais e épocas de semeadura para avaliação de genótipos de milho, quanto à produção de grãos nas cidades de Jaboticabal-SP e Campo Alegre de Goiás-GO. Foram conduzidos quatro experimentos no delineamento de blocos casualizados com três repetições e 17 genótipos sendo 13 sintéticos experimentais, três variedades e um hibrido comercial. Foram avaliadas duas épocas de cultivo para cada local. A estratificação ambiental foi mensurada pelo método tradicional de Lin (1982) e a dissimilaridade ambiental foi estimada pelo método de Cruz e Castoldi (1991), além da correlação de Pearson entre os pares de ambientes. Os resultados demonstraram que houve discordância entre os métodos utilizados. Nos programas de melhoramento, devem-se priorizar avaliações em anos e locais distintos, em detrimento de épocas de semeadura diferentes, a fim de discriminar os melhores genótipos e fazer as recomendações precisas dos mesmos
Keywords: Milho; Milho - Semeadura; Análise ambiental; Genetica vegetal; Produtividade agrícola; Plant-breeding